In Vitro Evaluation of Essential Oils Derived from Piper nigrum (Piperaceae) and Citrus limonum (Rutaceae) against the Tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae). (8th October 2017) - Vinturelle, Rafaelle; Mattos, Camila; Meloni, Jéssica; Nogueira, Jeane; Nunes, Maria Júlia; Vaz, Itabajara S.; Rocha, Leandro; Lione, Viviane; Castro, Helena C.; Chagas, Evelize Folly das
Abstract : The present research aimed to study the chemical composition and acaricidal activity of Citrus limonum and Piper nigrum essential oils against the cattle tick Rhipicephalus microplus . GC-MS analysis of C. limonum essential oil showed limonene (50.3%), β -pinene (14.4%), and γ -terpinene (11.7%) as the major components; P. nigrum oil was mainly composed of β -caryophyllene (26.2%), σ -ocymene (5.8%), and α -pinene (5.5%). Acaricide activity was evaluated at concentrations of 2.5, 5.0, and 10.0% (v/v) of each plant oil, as well as 1 : 1 combination of both oils (5% : 5%, 2.5% : 2.5%, and 1.25% : 1.25% each), by immersing engorged R. microplus females for one minute. The LC90 of oils from C. limonum, P. nigrum, and the combination were 4.9%, 14.8%, and 5.1%, respectively. C. limonum essential oil caused 100% mortality of engorged females at the highest concentration (10%). P. nigrum essential oil inhibited egg-laying by up to 96% in a concentration-dependent manner, suggesting it reduces tick fecundity. When combined, the oils presented toxicity as to C. limonum oil alone, but with stronger inhibition of oviposition (5% : 5%), indicating a possible additive effect against R. microplus . The present data provide support for further investigation of novel natural products to control bovine tick infestations.